PERANAN CHADIJAH ALI DALAM MEMAJUKAN PENDIDIKAN PEREMPUAN DI KOTA PEKANBARU 1946-1986 - Egi Septia Windari; Ridwan Melay M.Hum; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Chadijah Ali is a female figure who has struggled in advancing women's education in Pekanbaru city, an active in the organization and also a mubalighat. The purpose of this research was to know how the life history Chadijah Ali, to know the role of Chadijah Ali in advancing women's education, to know encouragement and obstacles faced by Chadijah Ali in an effort to promote women's education, to know the achievements Chadijah Ali in an attempt advancing education. The method used in this study is qualitative. Data were obtained from interviews and then analyzed by the language itself. The research location is Pekanbaru City, Riau Province. The research was started since the beginning of the title of this research essay submitted until this is completed. Data collection techniques used documentation techniques, interview techniques and engineering literature. The results showed that Chadijah Ali has a role in advancing the women's education in the city of Pekanbaru. Chadijah Ali is a female figure who actively organize and participate in setting up special school girls and also a school for boys and girls, such as establishing a Foundation for Women Unity of Islam, the Islamic Education Foundation, and the Foundation Diniyah Pekanbaru. Chadijah Ali role not only in education, but also in the health sector, with co-founded the Ibnu Sina Hospital, Islamic Hospital Foundation, which is still standing and serve the public in Pekanbaru City and from outside Pekanbaru.Keywords: Chadijah Ali, Women's Education, Pekanbaru City